Green Shipping Management - Lun, Y.H. Venus; Lai, Kee-hung; Wong, Christina W.Y; Cheng, T. C. E. (Shipping and Transport Logistics, 2016)
This book presents theory-driven discussion on the link between implementing green shipping practices (GSP) and shipping firm performance. It examines the shipping industry's challenge of supporting economic growth while enhancing environmental performance. Consisting of nine chapters, the book covers topics such as the conceptualization of green shipping practices (GSPs), measurement scales for evaluating GSP implementation, greening capability, greening and performance relativity (GPR), green management practice, green shipping network, greening capacity, and greening propensity. In view of the increasing quest for environment protection in the shipping sector, this book provides a good reference for firms to understand and evaluate their capability in carrying out green operations on their shipping activities.